Foreign language autonomy learning in law students’ professional education - Барская, А. А.; Barskaya, A. A. (Одеса : Фенікс, 2014)
Thus, students will undoubtedly become better prepared to make conscious decisions about what they can do to improve their learning with the help of this strategy. By monitoring their use of learning strategies, students are better able to keep themselves on track to meet their learning goals. Once they have selected and begun to implement specific strategies, they need to ask themselves periodically whether or not they are still using those strategies as intended. For this reason, developing law students foreign language autonomy learning during their professional education makes student highly motivated, goal oriented, well organized, hard working, initiative, enthusiastic about learning, flexible, active, willing to ask questions, making use of every opportunities to improve their learning.
Барская А. А. Foreign language autonomy learning in law students’ professional education / А. А. Барская // Правове життя сучасної України: матеріали Міжнар. наук. конф. проф.-викл. та аспірант. складу / відп. за вип. В. М. Дрьомін; НУ ОЮА, Півд. регіон. центр НАПрН України. – Одеса: Фенікс, 2014. – Т. 2. – С. 587-589.
Keywords: foreign language autonomy learning in law students’ professional education; обучение автономии иностранного языка в профессиональном образовании студентов-юристов; вивчення автономії іноземної мови в професійному навчанні студентів-юристів